Associations of Depressive Symptoms with COVID-19 Hospitalization or Death: The C4R Study - Elizabeth C. Oelsner; Yifei Sun; Pallavi P. Balte; Norrina B. Allen; Howard Andrews; April P. Carson; Yuni Choi; Shelley A. Cole; Talea Cornelius; David Couper; Mary Cushman; Martha Daviglus; et al. (Biopsychosocial Science and Medicine, 2026)
Objective: To investigate the relationship between depressive symptoms and risk for COVID-19 hospitalization and death in a United States general population-based sample. Methods: We studied participants enrolled into observational NIH-funded cohorts from 1971–2010 with ongoing follow-up through 2023. Pre-pandemic Centers for Epidemiologic Studies Depression (CES-D) 10-item scale scores ≥10 defined elevated depressive symptoms. Questionnaires, medical records, and death certificates classified incident COVID-19 as severe (hospitalized/fatal) or non-severe from April 2020 through February 2023. Results: Of 33,565 participants, 633 (1.9%) had incident severe COVID-19 over a mean (SD) follow-up of 453 (207) days. Elevated pre-pandemic depressive symptoms were present in 4,922 (16.3%) of participants. Elevated pre-pandemic depressive symptoms increased the hazard of severe COVID-19 in fully-adjusted (aHR=1.27; 95%CI: 1.03–1.57) models. In sex-stratified models (p-interaction=0.03), elevated depressive symptoms increased the hazard in women (aHR=1.49; 95%CI: 1.17–1.90) but not in men (aHR=0.96; 95%CI: 0.67–1.39). Conclusions: Pre-pandemic depressive symptoms were associated with increased risk of severe COVID-19 among women in a large US general population-based study of adults, and associations in men were neither confirmed nor ruled out. These results support current CDC recommendations that depression be considered an underlying medical condition associated with higher risk for severe COVID-19 and suggest that increased clinical focus on risk mitigation for COVID-19 and other acute respiratory infections among patients with depressive symptoms is warranted.